2019
DOI: 10.2967/jnumed.119.235093
|View full text |Cite
|
Sign up to set email alerts
|

Head-to-Head Comparison of 68Ga-DOTA-JR11 and 68Ga-DOTATATE PET/CT in Patients with Metastatic, Well-Differentiated Neuroendocrine Tumors: A Prospective Study

Abstract: Ga-DOTA-JR11 is a somatostatin receptor subtype 2-specific antagonist used for PET/CT imaging. The purpose of this study was to compare 68 Ga-DOTA-JR11 and 68 Ga-DOTATATE PET/CT in patients with metastatic, well-differentiated neuroendocrine tumors. Methods: Patients with histologically proven, metastatic or unresectable, well-differentiated neuroendocrine tumors were prospectively recruited to this study. Each patient received an intravenous injection of 68 Ga-DOTATATE (155 ± 52 MBq) on the first day and 68 G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 21 publications
0
55
2
2
Order By: Relevance
“…We also compared the therapeutic efficacy of 177 Lu-labeled DOTA-TATE, DOTA-JR11, and DOTA-EB-TATE, documenting the superiority of the latter in the mouse model characterized by high SSTR2 expression. There are several studies that suggested the superiority of SST antagonists over SST agonists (16,40,41). In our study, no significant difference was observed in the uptake of octreotate (TATE-agonist) vs JR11 (antagonist) linked to the same chelator (DOTA) in the tested mice models.…”
Section: Researchcontrasting
confidence: 54%
“…We also compared the therapeutic efficacy of 177 Lu-labeled DOTA-TATE, DOTA-JR11, and DOTA-EB-TATE, documenting the superiority of the latter in the mouse model characterized by high SSTR2 expression. There are several studies that suggested the superiority of SST antagonists over SST agonists (16,40,41). In our study, no significant difference was observed in the uptake of octreotate (TATE-agonist) vs JR11 (antagonist) linked to the same chelator (DOTA) in the tested mice models.…”
Section: Researchcontrasting
confidence: 54%
“…Radiolabeled SSTR2 antagonists, such as 177Lu-satoreotide tetraxetan, have shown higher tumor uptake, independent of SSTR activation, and greater tumor-to-organ ratios than agonists in preclinical models [ 160 ]. SSTR antagonists such as 68Ga-DOTA-JR11, [18F] AlF-NOTA-JR11, 68Ga-NODAGA-LM3 and 68Ga-DOTA-LM3, have demonstrated great sensitivity for the detection of NENs, potentially superior to [68Ga]Ga-DOTATATE [ 161 , 162 , 163 , 164 ]. A phase I study evaluated the efficacy and safety of 177Lu-satoreotide tetraxetan in 20 patients with advanced SSTR2-positive NETs [ 165 ].…”
Section: Somatostatin Receptors and Other Unique Targets In Netsmentioning
confidence: 99%
“…Patients that have received prior alkylating chemotherapy are at greater risk of developing MDS/acute leukemia following PRRT [158,159] Radiolabeled SSTR2 antagonists, such as 177Lu-satoreotide tetraxetan, have shown higher tumor uptake, independent of SSTR activation, and greater tumor-to-organ ratios than agonists in preclinical models [160]. SSTR antagonists such as 68Ga-DOTA-JR11, [18F] AlF-NOTA-JR11, 68Ga-NODAGA-LM3 and 68Ga-DOTA-LM3, have demonstrated great sensitivity for the detection of NENs, potentially superior to [68Ga]Ga-DOTATATE [161][162][163][164].…”
Section: Somatostatin Receptors and Other Unique Targets In Nets 41 Rmentioning
confidence: 99%
“…All scans were obtained in a three-dimensional model. 68 Ga-DOTA-TATE PET/CT Study The 68 Ga-DOTATATE was produced following our previously published procedure [13]. The study was carried out on a PET/CT scanner (Siemens Co.).…”
Section: F-fdg Pet/ct Studymentioning
confidence: 99%